Project-based learning integrated with local wisdom: Developing a trigonometry teaching module to enhance hots of senior secondary students in Merangin Regency - Indria Yulizarti; Endang Wahyuningrum; Sudirman Sudirman (Panicgogy International Journal, 2026)
This study developed and evaluated a trigonometry teaching module grounded in Project-Based Learning (PjBL) integrated with local wisdom from Merangin Regency, Indonesia, using the ADDIE development model. Needs analysis across three state senior secondary schools revealed that 80.2% of students found trigonometry difficult and 71.1% perceived mathematics as disconnected from daily life. The module, designed for tenth-grade students (Phase E) and aligned with Indonesia’s Merdeka Belajar curriculum, embedded the six-step PjBL syntax within contextual activities centred on the Tugu Pedang and Jam Gento—culturally iconic landmarks in Merangin Regency. Expert validation by three mathematics teachers yielded an overall feasibility score of 4.47 (89.49%), placing the module in the Very Feasible category. Practicality testing during a small-group trial (two teachers; ten students) indicated Very Practical ratings from teachers and Practical to Very Practical ratings from students across all assessed aspects. Large-group effectiveness testing employed a quasi-experimental non-equivalent comparison group design (n = 35 per class). The experimental class achieved a mean posttest Higher Order Thinking Skills (HOTS) score of 83.69 versus 65.45 in the control class, with classical mastery rates of 91.43% and 2.86% respectively. An independent-sample t-test confirmed a significant difference (Sig. = 0.000 < 0.05). These findings establish that the developed module is valid, practical, and effective, offering a replicable model for contextualising abstract mathematics through local cultural integration within project-based instructional frameworks. These findings are theoretically grounded in Project-Based Learning theory (Thomas, 2000) and Bloom’s revised taxonomy for HOTS (Anderson & Krathwohl, 2001), and are directed at tenth-grade (Phase E) students within Indonesia’s Merdeka Belajar curriculum framework.